Bond behaviour between NSM CFRP strips and concrete substrate using single-lap shear testing with epoxy adhesive. (15th November 2015) - Khshain, Nihad Tareq; Al-Mahaidi, Riadh; Abdouka, Kamiran
Abstract: The efficiency of near-surface mounted (NSM) carbon fibre reinforced polymer (CFRP) strengthening method depends on the bond between the concrete substrate and the NSM CFRP. Therefore, the behaviour of the bond between the concrete substrate and NSM CFRP strips must be understood. This paper presents the results of a study of the bond efficiency of NSM CFRP strips with two different dimensions (1.4 × 10, 1.4 × 20 mm) and surface types (smooth, rough). A total of 12 concrete prisms (75 × 75 × 250 mm) were tensioned under monotonic loading until failure using direct pull-out tests (single-lap shear tests). This paper also contains development of a statistical model to predict the bond strength (pull-out force). It was found that the rough surface of CFRP strips 1.4 × 20 mm in dimensions showed superior bond strength (pull-out force). Moreover, there is very good agreement between the experimental and predicted results.